Arabuluculuk ve tahkimi bir arada içeren uyuşmazlık çözüm yolu - Gökyayla, Cemile Demir (İstanbul hukuk mecmuası, 2019)
ÖZET: Çok basamaklı tahkim anlaşmalarında, tarafların, öncelikle arabulucuya başvuracakları ve uyuşmazlığın arabuluculuk yoluyla çözümlenememesi hâlinde tahkime başvurulabilecekleri kararlaştırılmaktadır (Arabuluculuk – Tahkim Yolu). Çok basamaklı tahkim anlaşmaları, uyuşmazlığın arabuluculuk yoluyla çözümlenememesi hâlinde tahkim yoluyla çözüleceğine dair taraf iradelerini herhangi bir tereddüde yer vermeyecek şekilde yansıtabiliyorsa geçerlidir. Taraflardan birisinin arabuluculuk yoluna hiç başvurmadan ya da süreç devam ederken tahkim yoluna başvurması hâlinde, hakemler öncelikle arabuluculuk yoluna başvurulmasının tahkim yoluna başvurulabilmenin bir ön koşulu olup olmadığını incelemelidir. Arabuluculuk bir ön koşulsa yargılamayı durdurup tarafların arabuluculuk aşamasına başvurmalarına ve arabuluculuk başarılı olmazsa tahkime devam edilmesine karar vermeleri gerekir. Arabulucunun hakem olarak da görev almasının isabetli olup olmadığı tartışmalıdır zira arabulucunun tahkim yargılamasında hakem olarak görev almasının önemli sakıncaları vardır. Amerika, Avrupa ve Türkiye’de benimsenen arabuluculuk ve tahkimle ilgili etik kurallara göre arabulucu ancak tarafların yazılı olarak muvafakat vermeleri hâlinde hakem olarak görev yapabilir. Bu hâlde bile, gizli bilgi ve belgelerin paylaşılması ve hakemin arabulucu olarak geliştirdiği önyargıları olması ihtimali vardır. Bir diğer husus da arabuluculuk aşamasında teati edilen bilgi ve belgelerin tahkim aşamasında delil olarak kullanılmasının hukuka uygun olup olmayacağı konusudur. Bu konuda arabuluculuk süreci nedeniyle ve bu sürece özgü olarak hazırlanan belgeler ve vakıaları ispata yarayan belgeler arasında ayrım yapılmaktadır.

ABSTRACT: Parties may agree that in the case of a dispute they shall first try to settle this dispute through mediation and only if the mediation fails may they start arbitration proceedings. Under Turkish law, such multi-tier dispute resolution clauses are valid to the extent that the parties’ intention to resort to arbitration is clear. In the case where one of the parties starts the arbitration without first invoking the mediation, the arbitral tribunal should interpret the arbitration agreement to determine whether the mediation is a pre-condition of arbitration. If the mediation is a pre-condition, the tribunal should suspend the arbitral proceeding for the parties to invoke the mediation. However, if the mediation fails, then the tribunal will resume the proceedings. The question of whether or not the mediator should also act as the arbitrator in relation to the same dispute is highly debatable because of the risks imminent thereto. Under the ethics rules accepted in the USA, in Europe and in Turkey, the mediator may act as arbitrator only if the parties agree thereon in written form. When the parties consent to the mediator acting as arbitrator there is still the risk of the mediator-arbitrator having prejudices because of the information and documents disclosed during the mediation proceedings. Another question is whether the information or documents disclosed throughout the mediation are admissible evidence at the arbitral proceedings. However, the solution is clear: while the documents prepared for the sole purpose of settling the dispute at the mediation are inadmissible, the documents related to the facts are admissible. In November 2019, Istanbul Arbitration Center (ISTAC) introduced its own Med-arb rules, namely the ISTAC Med-arb Rules. They are the first published institutional Med-arb rules and reflect the best practices in international mediation – arbitration. I am confident that ISTAC Med-arb Rules will be welcomed in the field of international dispute resolution with great enthusiasm.
Multi-tier dispute resolution clauses incorporating both mediation and arbitration together under Turkish law
Keywords: Tahkim; Hakem; Arabulucu Hakem kararlarının iptali; Delillerin kabul edilebilirliği; Arbitration in Turkey; Mediation in Turkey; Med-Arb; Admissibility of claim; Admissibility of evidence